Barbara Wheaton: Savouring the Past - Davidson, Alan E (Petits Propos Culinaires, 2024)
Barbara Wheaton: Savouring the Past - The French Kitchen and Table from 1300 to 1789: University of Pennsylvania Press, Philadelphia PA, 1983: 352 pages, numerous black and white illustrations (mostly from old books), 20 pages bibliography, clothbound, 35.00, paperback 17.95 (and Chatto and Windus are publishing a hardback edition in the UK at £15.00).